2006
DOI: 10.1111/j.1475-3588.2006.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Illness Beliefs in Chronic Fatigue Syndrome: A Study Involving Affected Adolescents and their Parents

Abstract: Background:  The aim of the study was too investigate the beliefs of young people with Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME) and their parents, about illness causes and management. Method:  Twenty‐one young people with CFS/ME and their parents participated in an open‐ended interview. Results:  Infective causes were identified by the majority of respondents, and psychological ones by a minority. Many highlighted reducing activity and resting in symptom management. Positive and negative exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 17 publications
3
32
0
Order By: Relevance
“…There is also a need for patient with CFS to be recognised and listened to, both by professionals and by society (Richards et al . ). A previous study of adolescent CFS pointed out five different challenges related to being ill.…”
Section: Introductionmentioning
confidence: 97%
“…There is also a need for patient with CFS to be recognised and listened to, both by professionals and by society (Richards et al . ). A previous study of adolescent CFS pointed out five different challenges related to being ill.…”
Section: Introductionmentioning
confidence: 97%
“…The few studies conducted on children and young patients with CFS/ME have found similar attributions and coping patterns as with adults [11]. In this explorative study, our aim was to adapt a qualitative methodology to the questions of attribution and coping strategies by using a semi-structured interview.…”
Section: Introductionmentioning
confidence: 99%
“…As the understanding of CFS/ME in young people is relatively poor and, with a few exceptions [10,11], qualitative research on this patient population is meagre, existing literature and national guidelines for young patients with CFS/ME have emphasised the need for further quantitative and qualitative research [12][13][14]. As information obtained from research into the adult population is not necessarily applicable to young patients [11,12], and beliefs of the patients in their own terms is not necessarily best captured by quantitative inquiry using standard questionnaires, we wanted to explore in-depth the illness experience of young patients with CFS/ME by using a qualitative methodology. More specifically, we wanted to investigate the nature and function of two aspects of adolescents' illness experience: attribution and coping strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have described how young people with NES and other types of MUS feel that their identity is under threat when their credibility is questioned [4,24]. They describe a lack of trust from the healthcare services, and difficult feelings due to the contentious and uncertain condition [4,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%